Peningkatan Pengetahuan Kesehatan Reproduksi Remaja Putri Melalui Edukasi Menstruasi Sehat dan Personal Hygiene di Pondok Pesantren Assa’adah Maros - Andi Asrina; Yusriani Yusriani; Fairus Prihatin Idris; Yudha Pamungkas; Andi Hariati5; Indah Mustikasari; Widia Ramadhany (Faedah: Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
Background: Adolescent reproductive health remains a significant public health issue, particularly among female adolescents who frequently encounter misconceptions regarding menstruation and inadequate personal hygiene practices. Limited reproductive health literacy may increase the risk of reproductive tract infections, school absenteeism, and poor quality of life. Educational interventions based on participatory health promotion are expected to improve adolescents' knowledge and healthy behaviors. Objective: This community service program aimed to improve female adolescents' knowledge regarding reproductive health, healthy menstruation, menstrual hygiene management, and personal hygiene through structured educational interventions. Methods: The program employed a participatory educational approach using interactive lectures, group discussions, demonstrations, educational games, simulations, and pretest–posttest evaluation. Participants consisted of female students aged 12–18 years at Pondok Pesantren Assa'adah Maros. Educational materials included female reproductive anatomy, puberty, menstrual physiology, menstrual hygiene management, dysmenorrhea management, myths and facts regarding menstruation, and safe sanitary pad selection. Results: The educational intervention demonstrated an increase in participants' reproductive health knowledge as reflected by improvements in posttest scores compared with pretest results. Participants also demonstrated better understanding regarding menstrual hygiene practices, menstrual cycle monitoring, and appropriate reproductive health behaviors. Conclusion: Participatory reproductive health education effectively improves adolescents' knowledge and awareness regarding menstrual health and personal hygiene. Continuous collaboration among schools, pesantren, health professionals, and higher education institutions is recommended to sustain adolescent reproductive health promotion.